2011
DOI: 10.1152/ajplung.00166.2011
|View full text |Cite
|
Sign up to set email alerts
|

Delayed stress fiber formation mediates pulmonary myofibroblast differentiation in response to TGF-β

Abstract: Myofibroblast differentiation induced by transforming growth factor-β (TGF-β) and characterized by de novo expression of smooth muscle (SM)-specific proteins is a key process in wound healing and in the pathogenesis of fibrosis. We have previously shown that TGF-β-induced expression and activation of serum response factor (SRF) is required for this process. In this study, we examined the signaling mechanism for SRF activation by TGF-β as it relates to pulmonary myofibroblast differentiation. TGF-β stimulated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
111
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 89 publications
(120 citation statements)
references
References 90 publications
7
111
1
Order By: Relevance
“…This contractile activity can be transduced to nuclear signaling events by a process known as mechanotransduction (58). Indeed, our group has previously shown that the transcription factor MKL1 translocates to the nucleus under conditions of stress fiber formation and active contraction; a Rho kinase inhibitor that depolymerizes filamentous actin (F-actin) to globular actin (G-actin) inhibits the cytoplasmic-nuclear translocation of MKL1 and suppresses myofibroblast differentiation (9,10). Whether the integration of cellular bioenergetics to signaling of myofibroblast differentiation in our system involves MKL1 requires further study.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…This contractile activity can be transduced to nuclear signaling events by a process known as mechanotransduction (58). Indeed, our group has previously shown that the transcription factor MKL1 translocates to the nucleus under conditions of stress fiber formation and active contraction; a Rho kinase inhibitor that depolymerizes filamentous actin (F-actin) to globular actin (G-actin) inhibits the cytoplasmic-nuclear translocation of MKL1 and suppresses myofibroblast differentiation (9,10). Whether the integration of cellular bioenergetics to signaling of myofibroblast differentiation in our system involves MKL1 requires further study.…”
Section: Discussionmentioning
confidence: 91%
“…Myofibroblast Contraction and Differentiation Are Dependent on Mitochondrial Bioenergetics and Glycolysis-Contraction of myofibroblasts has been shown to promote myofibroblast differentiation (9,10,56). We determined whether the increase in mitochondrial biogenesis/bioenergetics is necessary to mediate contractility of differentiated myofibroblasts.…”
Section: Tgf-␤1 Activates Metabolic Reprogramming Via a P38 Mitogen-amentioning
confidence: 99%
“…We and others have established previously that this process is initiated by Smad-dependent expression of intermediate signaling molecules driving the activation of SRF that is required for the expression of SM-␣-actin, collagen 1, and other myofibroblast differentiation markers (13,14,31). We also showed that activation of SRF by TGF-␤ in HLF is mediated by increased expression and nuclear accumulation of SRF co-activator MKL1 and that this process is blocked by microtubule stabilizer, Taxol (14,18). As shown in Fig.…”
Section: Antifibrotic Effects Of Noscapine In Vitro and In Vivo-mentioning
confidence: 99%
“…In Vitro Isolation of Stress Fibers-Stress fibers were isolated as described previously (14,18). All of the procedures were performed on ice using buffers containing protease inhibitors (Sigma).…”
Section: Primary Culture Of Human and Mouse Lung Fibroblasts-mentioning
confidence: 99%
See 1 more Smart Citation